On some new properties of catalan numbers. - Sattarovich, Rakhimov Isamiddin; Mohd Atan, Kamel Ariffin (World Scientific Publishing, 2012)

(untitled)
It is well known that Catalan Numbers are used in Mathematical Biology as Enumerating RNA secondary structures for finite points. In this paper, we present some new properties of the Catalan Numbers.